2005
DOI: 10.2139/ssrn.739664
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Price-Earnings Ratio

Abstract: The price-earnings effect has been thoroughly documented and is the subject of numerous academic studies. However, in existing research it has almost exclusively been calculated on the basis of the previous year's earnings. We show that the power of the effect has until now been seriously underestimated due to taking too short-term a view of earnings. Looking at all UK companies since 1975, using the traditional P/E ratio we find the difference in average annual returns between the value and glamour deciles to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…This could be generalized for investment decision on other companies from other industries. The outcomes of this study constant with a study done earlier which found strongly significant and positive effect of profitability toward company's overall efficiency and performance, as in [18].…”
Section: Conclusion and Recommendationsupporting
confidence: 85%
See 1 more Smart Citation
“…This could be generalized for investment decision on other companies from other industries. The outcomes of this study constant with a study done earlier which found strongly significant and positive effect of profitability toward company's overall efficiency and performance, as in [18].…”
Section: Conclusion and Recommendationsupporting
confidence: 85%
“…In other words, high TATO and low PE is a best set of indicator for company's performance. Reference [18] mentioned in their study that the increment on company's PE actually means they get slightly worse over long holding periods. Reference [19] mentioned TATO has negative correlation with stock return.…”
Section: Discussionmentioning
confidence: 99%
“…12 Evidence of low P/E ratios generating abnormal returns is well documented in studies by Basu (1975Basu ( , 1977Basu ( , 1983; Keim (1988);Lakonishok et al (1994); Gregory et al (2001Gregory et al ( , 2003 and Anderson and Brooks (2006), to cite a few. As reported for the dividend-price ratio in Table 2, the LKT results for the priceearnings ratio suggest the existence of two I(1) periods.…”
Section: Robustness and The Pwy Testmentioning
confidence: 93%